Assessment of the 4‐week repeated‐dose oral toxicity and genotoxicity of GHX02. Issue 2 (12th September 2019) - Ji, Kon‐Young; Kim, Ki Mo; Oh, Jeong‐Ja; Kim, Jung‐Woo; Lee, Woo‐Joo; Cho, Hyeon; Lee, Hyun‐Kul; Lee, Joo Young; Chae, Sungwook
Abstract: Herbal medicines are widely utilized for disease prevention and health promotion. GHX02 consists of mixtures including Gwaruin ( Trichosanthes kirilowii ), Haengin ( Prunus armeniaca ), Hwangryeon ( Coptis japonica ) and Hwangkeum ( Scutellaria baicalensis ). It has been purported to have therapeutic effectiveness in cases of severe bronchitis. Non‐clinical safety testing comprised a single‐dose oral toxicity study and a 28‐day repeated‐dose oral toxicity study with a 14‐day recovery period, and genotoxicity was assessed by a bacterial reverse mutation test, in vitro chromosomal aberration test, in vivo mouse bone marrow micronucleus test and single cell gel electrophoresis assay (comet assay). In the single‐dose oral toxicity study, the approximate lethal dosage is estimated to be higher than 5000 mg/kg in rats. Thus, the dosage levels were set at 0, 1250, 2500 and 5000 mg/kg/day in the 28‐day repeated‐dose oral toxicity study, and 10 male rats and 10 female rats/dose were administered GHX02. No clinical signs of toxicological significance were recorded in any animal during the dosing and the observation period in the single‐dose study. The no‐observed‐adverse‐effect level of GHX02 was 5000 mg/kg/day when administered orally for 28 days to male and female Sprague‐Dawley rats. Despite increases in the frequencies of cells with numerical chromosomal aberration in the in vitro test, the increases were not considered relevant to the in vivo genetic risk. Except for the increase of in vitro numerical chromosomal aberration, clear negative results were obtained from other genetic toxicity studies. Abstract : GHX02 consists of mixtures including Gwaruin, Haengin, Hwangryeon and Hwangkeum. This study aimed to evaluate the 4‐week repeated‐dose oral toxicity and genotoxicity of GHX02. GHX02 exhibits no general toxic and genotoxic effects and the no‐observed‐adverse‐effect level of GHX02 could be established in 5000 mg/kg/day in both male and female Sprague‐Dawley rats.